Death...your time is up! - Khalid Yasin; One Islam Productions (N.S.W, Australia : One Islam Productions, 2006)
Khalid Yasin gives an intense lecture on the topic of death in islamic life
Title from title screen
Lecturer : Khalid Yasin
Keywords: Death -- Religious aspects -- Islam; Death